Risk factors for relaparotomy after a cesarean delivery: a case-control study - Uri Amikam; Yael Botkovsky; Alyssa Hochberg; Aviad Cohen; Ishai Levin; Yariv Yogev; Liran Hiersch; Anat Lavie (BMC, 2024)
Abstract Background Relaparotomy following a cesarean delivery (CD) is an infrequent complication, with inconsistency regarding risk factors and indications for its occurrence. We therefore aimed to determine risk factors and indications for a relaparotomy following a CD at a single large tertiary center. Methods A retrospective case-control single-center study (2013-2023). We identified all women who had a relaparotomy up to six weeks following a CD (study group). Maternal characteristics, obstetrical and surgical data were compared to a control group in a 1:2 ratio. Controls were women with a CD before and immediately after each case in the study group, who did not undergo a relaparotomy. Included were CDs occurring after 24 gestational weeks. CD performed at different centers and indications for repeat surgery unrelated to the primary surgery (e.g., appendicitis) were excluded. Logistic regression was used to adjust for potential confounders. Results During the study period, 131,268 women delivered at our institution. Of them, 28,280 (21.5%) had a CD, and 130 patients (0.46%) underwent a relaparotomy. Relaparotomies following a CD occurred during the first 24 h, the first week, and beyond the first week, in 59.2%, 33.1%, and 7.7% of cases, respectively. In the multivariable logistic regression analysis, relaparotomy was significantly associated with Mullerian anomalies (aOR 3.33, 95%CI 1.08-10.24, p = 0.036); uterine fibroids (aOR 3.17, 95%CI 1.11-9.05,p = 0.031); multiple pregnancy (aOR 4.1, 95%CI 1.43-11.79,p = 0.009); hypertensive disorders of pregnancy (aOR 3.46, 95%CI 1.29-9.3,p = 0.014); CD during the second stage of labor (aOR 2.54, 95%CI 1.15-5.88, p = 0.029); complications during CD (aOR 1.62, 95%CI 1.09-3.21,p = 0.045); and excessive bleeding during CD or implementation of bleeding control measures (use of tranexamic acid, a hemostatic agent, or a surgical drain) (aOR 2.23, 95%CI 1.29-4.12,p = 0.012). Indications for relaparotomy differed depending on the time elapsed from the CD, with suspected intra-abdominal bleeding (36.1%) emerging as the primary indication within the initial 24 h. Conclusion We detected several pregnancy, intrapartum, and intra-operative risk factors for the need for relaparotomy following a CD. Practitioners may utilize these findings to proactively identify women at risk, thereby potentially reducing their associated morbidity.